New emphases for adult education in the Caribbean in the eighties. Final report (UNESCO Regional Office for Education in Latin America and the Caribbean, 1980)
A meeting was held in St. Lucia in September, 1980, at which representatives of Caribbean countries discussed the present state and future progress of adult education in the region. The meeting viewed adult education as a vital part of national and regional development. Meeting participants stressed the following four themes: 1) political changes that require adult education in order that the people may understand and be involved in the developmental process; 2) the continuing economic development of the countries and their growing industries; 3) the growing unrest of youth and the spread of new behavioural patterns, requiring new approaches to education; and 4) environmental conditions, especially natural disasters, which have increased the need for education for disaster preparedness at the national and regional levels. Innovations in adult education noted in some of the countries included literacy education, pre-university academic courses, and technical and vocational training. Recommendations were made for the integration of adult education in the overall administrative structure of the countries; for needed legislation supporting adult education; for mutual assistance between the formal and nonformal systems of education; for administrative structures for adult education; for sound financing of adult education; for research into adult education needs and structures; for a research library and communication centre; and for training of adult education teachers
Keywords: Adult education